Lithuanian Cultural Landscape in Folklore from the Perspective of Values - Stundžienė, Bronė (Vilnius University Open Series, 2020)
In the article, the contemporary human being’s search for values is primarily linked to the folkloristic reflection of Lithuanian cultural landscape. Following the framework of hermeneutics and based on the folkloristic symbolism of landscape in Lithuanian folklore (mainly in the oldest layer of folk songs), the manifestations of a long-lasting solidarity between community and nature are discussed. The focus has been placed on the small community – the family and its immediate relationship with the surrounding nature. In the introductory part of the article, the notion of ritualism is discussed which is based on the universally acknowledged concept of the rites of passage (les rites de passage). Within the context of this concept, the depiction of the public events of family life (the rituals of marriage and death) constituted a solid premise for the investigation of the so-called common places (loci communes) in Lithuanian folk poetry, which in this regard are usually represented by landscape-related narrative segments and symbolism. Folkloristic interpretations of the prominent elements of Lithuanian landscape (trees, water, stones) have been selected for the investigation. The introduction also reveals the importance of a family over an individual in the exploration of a human being’s relationship with the surrounding nature. The first part of the article ‘The Reflections of Anthropomorphic Reception of Trees’ asserts that in the folk songs marked by archaic stylistics, the poetic narrative of trees contains abundant mythopoetic allusions to the constant identification of a human being (usually, a family member) with a tree, as well as other metamorphoses and motifs which attest their mutual dependence. This poetic tradition influences the poetry created by individual authors to this day. The article briefly introduces the meaning of a tree in the world of ancient Lithuanian beliefs and customs and notices the major changes in the purpose of the image of a tree in the late tradition of romances. The second part of the article analyses the long-term trajectories of mythopoetic depiction of water and stones in folklore. It is well known that any traditional culture has accumulated a wide range of meanings which pertain to different forms of water and connote rebirth, renewal, as well as fertility and life. Therefore when the article emphasizes the tropes of being near water, drowning in watery depths, which through the lens of myth and ritual embody the act of love (marriage) in Lithuanian singing folklore, it should be noted that this variation of meaning found in Lithuanian folklore constitutes an organic part of the whole of international aquatic symbolism. The mythicised story of a live stone as reflected in folklore could be partially associated with the folkloristic reception of trees and water. Animation of a stone is revealed through the attribution of the qualities of a live being to a stone (in the legends, they move, communicate with each other, live in families). Contrarily, the lifelessness (immobile state) of a stone is mythicised in cases where people who deviate from moral laws are turned into stones. The mythologem of a stone as the landmark signifying the boundary between this and the other world, as well as the association of stones with sacrality and sacred places visited by deities, is widespread. It is ascertained that the narrative of the sacrality of stones did not cease in the period of Christianity.Therefore, the landscape approach applied in this study provided a possibility to observe how, in folklore, the meanings of different components of landscape organically combine into a cohesive union which operates on the principles of synergy. A conclusion may be drawn that folklore unequivocally asserts the idea of a continuous coexistence of a human being and nature and exalts the perception of nature as an essential spiritual value.
Keywords: landscape; folklore; family; song; tree; water; stone; value